TRANSFORMASI DIGITAL: PENGARUH KEPEMIMPINAN DIGITAL, KAPABILITAS DIGITAL, DAN KEMAMPUAN DINAMIS KARYAWAN TERHADAP KINERJA DIGITAL KARYAWAN DI PERUSAHAAN AVIASI - Alya Hafizhah Azzahra; Tiara Puspa (STMIK Widuri Jakarta, 2025)
Digital transformation in the aviation industry requires technical capability enhancement, innovative leadership, and employee agility to support technology-driven performance. This study examines the effects of digital leadership, digital capability, and employee dynamic capability on employee digital performance at PT Apex Aviation and PT Prima Air Charter. A quantitative approach using SEM-AMOS was applied to data from 100 ground handling staff. All five hypotheses were supported at the 99% confidence level: digital capability → dynamic capability (β = 0.390), digital leadership → digital capability (β = 0.450), dynamic capability → digital performance (β = 0.319), digital capability → digital performance (β = 0.367), and digital leadership → digital performance (β = 0.336). Findings highlight that successful digital transformation demands coordinated investment in technology, leadership development, and strengthening of dynamic capabilities to achieve superior digital performance in ground handling services.